(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
Surabaya, as the second-largest metropolitan city in Indonesia, faces increasing challenges of population density and limited land availability. To address these issues, the Surabaya City Government has adopted the development of Simple Owned Flats (Rusunami) as a strategic solution. Rusunami is designed as an affordable vertical housing option for low-income communities, aiming to provide decent housing amidst rapid urbanization and economic growth. This program is part of the national "one million homes" initiative, with planned construction in five strategic locations: Tambak wedi, Gunung Anyar, Kedung Cowek Menanggal, dan Bulak banteng. This initiative is expected to reduce residential overcrowding while offering an efficient housing solution for the people of Surabaya.